2018
DOI: 10.1182/blood-2018-02-830844
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin vs observation in childhood immune thrombocytopenia: a randomized controlled trial

Abstract: Key Points In children with newly diagnosed ITP, IVIg treatment at diagnosis does not result in a lower rate of chronic ITP. Upfront treatment with IVIg led to faster recovery and less severe bleeding events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(128 citation statements)
references
References 33 publications
1
118
0
Order By: Relevance
“…Immune thrombocytopenia (ITP) is an acquired immune‐mediated disorder, characterised by an isolated thrombocytopenia which results in an increased risk of bleeding. In children, bleeding symptoms are usually mild (Neunert et al , ) and the spontaneous remission rate is high, with 75–80% of children recovering within 12 months of presentation (Imbach et al , ; Heitink‐Pollé et al , , ). In light of this, most children in the UK with ITP do not receive therapy directed at raising the platelet count, but are managed on an expectant ‘watch and wait’ policy (Grainger et al , ).…”
mentioning
confidence: 99%
“…Immune thrombocytopenia (ITP) is an acquired immune‐mediated disorder, characterised by an isolated thrombocytopenia which results in an increased risk of bleeding. In children, bleeding symptoms are usually mild (Neunert et al , ) and the spontaneous remission rate is high, with 75–80% of children recovering within 12 months of presentation (Imbach et al , ; Heitink‐Pollé et al , , ). In light of this, most children in the UK with ITP do not receive therapy directed at raising the platelet count, but are managed on an expectant ‘watch and wait’ policy (Grainger et al , ).…”
mentioning
confidence: 99%
“…The preliminary results, presented in abstract form at the 2016 ASH annual meeting, indicated no difference in the rates of persistent disease at 6 months between the two groups (10.2% in the IVIg group and 10.4% in the observation group). 42 The study did show a lower incidence of grade 4 or 5 bleeding in IVIg group compared with placebo (8% vs 1%); however, given the low rates of bleeding, the number needed to treat does not justify exposure of all children to IVIg. There have been no additional randomized trials in pediatric ITP with a primary aim of preventing chronic disease.…”
Section: Pediatric Considerationsmentioning
confidence: 86%
“…In this issue of Blood, Hu et al elegantly demonstrate that steroid receptor coactivator-3 (SRC-3) is essential for maintenance of hematopoietic stem cell (HSC) homeostasis via repression of mitochondrial biogenesis by acetyltransferase GCN5-mediated posttranslational modification of peroxisome proliferator-activated receptor g coactivator 1-a (PGC-1a). 1 The metabolic phenotype of a cell is emerging as a critical determinant of the fate of stem cells. This is also true for HSCs with a number of players in the metabolic rewiring of HSCs already described.…”
Section: Mitochondria Confirmed As Drivers Of Hsc Fatementioning
confidence: 99%
“…Finally, the health-related quality of life (HRQoL) analysis of 107 of the 200 TIKI trial patients (published separately) 8 showed a significant improvement in HRQoL in patients achieving a complete platelet response as was stated in the complete report. 1 Importantly, these were all prospective observations from a trial with an apparent very high rate of compliance: all patients were included in the analysis. One important caveat was that no premedication was given with the IVIg infusions.…”
mentioning
confidence: 99%